Pelatihan Pembuatan Donat Praktis dengan Metode Autolisis di Lingkungan Dharma Wanita Persatuan Fakultas Teknik Universitas Riau - Nurfatihayati Nurfatihayati; Anisa Mutamima; Cory Dian Alfarisi; Drastinawati Drastinawati; Yelmida A (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2022)
Doughnuts are one of the most popular sweet foods for people of all ages around the world. Although made from simple ingredients such as flour, sugar, eggs, yeast, milk powder, salt, water, and margarine, however producing doughnuts requires special techniques to produce good-quality doughnuts. It needs more energy, even physically and electrical equipment. A workshop on doughnut production with autolyze method for Dharma Women Association, Faculty of Engineering, University of Riau, was conducted to increase the knowledge and skills of members of the organization in making healthy dishes for the family. In this workshop, doughnuts were made using the autolysis method, which is mixing bread flour with water and then keeping the dough until gluten was formed. The formation of gluten is one indicator of the formation of smooth, soft, and elastic dough. The workshop results showed high interest among the Dharma Women Association members in making doughnuts with this alternative method.